A review on fabrication methods, reinforcements and mechanical properties of aluminum matrix composites - Chak, Vineet; Chattopadhyay, Himadri; Dora, T L (Journal of manufacturing processes, 2020)
A tremendous rise in application of aluminium matrix composite in various engineering applications have been witnessed in the recent years. Aerospace, defense and automobile sectors are using increased number of parts made from aluminium matrix composites. Components made from aluminium based composites, as compared to monolithic materials, offer superior properties like high strength to weight ratio, strength, stiffness, hardness and tribological behavior. The properties of aluminium matrix composites are highly dependent of appropriate selection of aluminium matrix, reinforcement material and processing route for its fabrication. The current study attempts to present an overview on the available fabrication routes, reinforcement materials, pertinent research issues and challenges in production of aluminium matrix composites. Special attention is focused on the mechanical properties of fabricated aluminium matrix composites.